A Study of the Demography, Etiological Profile and Risk Factors of Acute Viral Hepatitis in an Urban Setting - Varsha R Bhatt; Ramdas B Barure (Medsci Publications, 2017)
Background: Acute Viral Hepatitis (AVH) is a major public health problem in India. The objectives of this study were to elucidate the demography, etiological profile, risk factors and comparative clinical spectrum of AVH transmitted faeco-orally and parenterally in an urban setting in Western India. Methodology: 100 patients more than 12 years of age having jaundice with raised alanine transaminase and serology positive for acute markers of hepatitis viruses A,E,B,D and C were included in this study over a period of eighteen months.The data was analyzed using SPSS (2015 version). Results: 73% patients were in the under 30 year age group. 70% were males. 53% had Hepatitis E, 34% had Hepatitis A, 11% had Hepatitis B and 2% had Hepatitis C .79% had one or other risk factors such as close personal contact, travel, mass gathering, eating roadside food, blood transfusion, injection use and high risk behaviour. Clinical severity and the serum bilirubin levels were statistically higher in the faeco-orally transmitted hepatitis than the parenterally transmitted one. The mean duration of illness was 17.1+ 6.8 days and the mean numbers of days lost from work were 22.2 + 5.6 days. Conclusion: In this study, younger male population seemed more affected. Most patients had preventable risk factors. Results suggested a heavy socioeconomic burden of the disease.